PELAKSANAAN PERLINDUNGAN ANAK SEBAGAI SAKSI KORBAN KEKERASAN RUMAH TANGGA (Studi di Wilayah Hukum Pengadilan Negeri Denpasar) - Ali Wardana, I Ketut; Rai Setiabudhi, I Ketut; Surya Darma Jaya, Ida Bagus (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 05, Oktober 2014)
The purpose of this study is to investigate the implementation of protection andthe factors that affect of the implementation of children protections as victims? of domestic violence, particularly in Denpasar District Court Jurisdiction.The method of data collectionis conducted by the method of literature and interview methods. The datacollected was analyzed qualitatively and comprehensive. The results showed that (1)the protection of children as victims of domestic violence contained in thelegislation, namely Law No.23 year2002 about child protection, Article64 (3). It isimplemented infull,both the police and in the courts. In the formof rehabilitation, protection coverage(labeling), safety assurance, and providing information about the caseat hand. (2) Factors that support and hinder the implementation of the legal protection factor ofthe law itself, the law enforcement factor, factor means orfacilities, community factors and cultural factors.
Keywords: Protection of Child, Victim Witness, Domestic Violence